Bargaining and Power - Dominik Karos (Fondazione Eni Enrico Mattei (FEEM), 2013)
Given a simple game, a power configuration specifies the power of each player in each winning coalition. We introduce a new power configuration which takes into account bargaining among players in coalitions. We show that under very weak conditions on a bargaining solution there is a power configuration which is stable with respect to renegotiations. We further show that given this power configuration there is a coalition which is both internally and Nash stable. We consider two different bargaining solutions on apex games and show under which conditions there are core stable coalitions. Finally, we investigate how infeasible coalition might affect the outcome and apply our model to the German parliament.
Keywords: C71; D71; 330; Coalition Formation; Power; Bargaining